The impact of the human talent management strategy on promoting a culture of educational innovation in the training department in the Greater Salt Municipality - Alkhreasat, Hiba Thabet (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed to identify the impact of the human talent management strategy on promoting a culture of educational innovation in the training department in the Greater Salt Municipality. The research sample consisted of (26) respondents from administrators and workers in the training department in the Greater Salt Municipality. The research reached a number of results, the most important; which are that there is a degree of good agreement among the study sample regarding the level of the human talent management strategy in the training department in the Greater Salt Municipality. And that there is a strong degree of agreement among the members of the study sample for planning manpower in the training department in the Greater Salt Municipality, but it differs between them in the way they are prepared and organized.The research also found that there is a good degree of agreement among respondents regarding the level of attracting human talent in the training department of the Greater Salt Municipality. And that there is a good degree of agreement among the sample members about the level of human talent development in the training department in the Greater Salt Municipality. And that there is a good degree of agreement among the sample members of the involvement of human talents and their retention in the training department in the Greater Salt Municipality. The research also found that there is a strong degree of agreement among the study sample members of the role of the training department in promoting the culture of educational innovation in the Greater Salt Municipality. Among the other important findings of the research is the existence of a statistically significant effect at a significant level (α≤0.05) of the human talent management strategy in university administration on enhancing the culture of educational innovation in the training department in the Greater Salt Municipality.
Keywords: human talent strategy; promoting a culture of educational innovation; training department; Greater Salt Municipality